2015
DOI: 10.15453/2168-6408.1129
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Transition to College for Students Diagnosed with Asperger’s Disorder

Abstract: Background: Obtaining a college degree is a positive and often necessary step to adulthood, independence, and knowledge. Students diagnosed with Asperger's Disorder (AD) typically experience difficulty in college, especially in the transition to college. To assist students with AD in the transition to college, an occupational therapy mentoring program was developed in a college setting. This article describes this program, provides quantitative and qualitative outcomes of the program, and uses the outcomes to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 16 publications
0
44
0
Order By: Relevance
“…Of the final 25 articles, two of them were qualitative designs (Berg, Jirikowic, Haerling, & MacDonald, 2017;McCausland, Bazyk, & Kerns, 2012). Ten articles of the final 25 were primarily descriptive in nature (Best, Still, & Cameron, 2008;Burnett-Beaulieu, 1984;Burnett & Yerxa, 1980;Burson, 2003;Eichler, Hoevet, & Royeen, 2015;Eichler & Royeen, 2016;Jacobs, Selby, & Madsen, 1996;Nolan & MacCobb, 2006;Smallfield, Benda, & Siefkes, 2011), while 11 articles were intervention studies (Gutman, Kerner, Zombek, Dulek, & Ramsey, 2009;Keptner et al, 2016;Keptner, 2017;Lewis & Nolan, 2013;Malcolm & Roll, 2019;Quinn, Gleeson, & Nolan, 2014;Schindler, 2014;Schindler, 2018;Schindler, Cajiga, Aaronson, & Salas, 2015;Schindler & Sauerwald, 2013).…”
Section: Results Descriptive Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Of the final 25 articles, two of them were qualitative designs (Berg, Jirikowic, Haerling, & MacDonald, 2017;McCausland, Bazyk, & Kerns, 2012). Ten articles of the final 25 were primarily descriptive in nature (Best, Still, & Cameron, 2008;Burnett-Beaulieu, 1984;Burnett & Yerxa, 1980;Burson, 2003;Eichler, Hoevet, & Royeen, 2015;Eichler & Royeen, 2016;Jacobs, Selby, & Madsen, 1996;Nolan & MacCobb, 2006;Smallfield, Benda, & Siefkes, 2011), while 11 articles were intervention studies (Gutman, Kerner, Zombek, Dulek, & Ramsey, 2009;Keptner et al, 2016;Keptner, 2017;Lewis & Nolan, 2013;Malcolm & Roll, 2019;Quinn, Gleeson, & Nolan, 2014;Schindler, 2014;Schindler, 2018;Schindler, Cajiga, Aaronson, & Salas, 2015;Schindler & Sauerwald, 2013).…”
Section: Results Descriptive Summarymentioning
confidence: 99%
“…Student outcomes were positive after participation in occupational therapy programming. Positive outcomes included higher enrollment in an academic program after participation (Gutman et al, 2009;Schindler et al, 2015;Schindler & Sauerwald, 2013), improved academic skills, increased competency in student role, enhanced social skills and professional behaviors, and more confidence . Jacobs, Selby, and Madsen (1996) reported improved individual goal attainment among students with common goals, including coping with stress, extending social outlets, improving study skills, selfawareness, and self-esteem, decreasing negative self-talk, exploring leisure activities, and decreasing anxiety.…”
Section: Results Descriptive Summarymentioning
confidence: 99%
“…Indeed, it is impossible to rule out the possibility that apparent benefits of programming designed for neurodiverse students reported in the current study and in prior literature have been entirely attributable to the opportunities to engage with peers that such programming provides as all (to the best of our knowledge) of the extant published research examining supports for autistic college students and college students with other disabilities has been quasi-experimental (e.g., Bat-Hayim, 1997; Parker et al, 2011; Harrison et al, 2012; Mytkowicz and Goss, 2012; Getzel, 2014; Pugliese and White, 2014; White et al, 2014; Prevatt and Yelland, 2015; Schindler et al, 2015; Ames et al, 2016). Indeed, many students in the current study reported that their favorite part of the mentorship program remained the opportunities it provided to socialize with peers in an environment where differences were respected, irrespective of the curricular topic.…”
Section: Discussionmentioning
confidence: 99%
“…These difficulties include atypical sensory processing, inflexibility, executive function difficulties, challenges engaging in self-advocacy, social difficulties, depression, and anxiety (Glennon, 2001; Van Bergeijk et al, 2008; White et al, 2011; Schindler et al, 2015; Cai and Richdale, 2016). The stress that most students experience when transitioning into college may be compounded for autistic students, as difficulty in coping with change is part of the diagnostic criteria for ASD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation